Analisis Faktor-Faktor yang Mempengaruhi Keputusan Berinvestasi di Pasar Modal Syariah: Studi pada Mahasiswa Prodi Ekonomi Syariah UIN Fatmawati Sukarno Bengkulu - Anike Putri; Mursalin, Supardi; Stiawan, Evan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of this research is to determine the influence of internal factors and external factors on the decision to invest in the sharia capital market among students of the Sharia Economics Study Program at UIN Fatmawati Sukarno Bengkulu. To test this, researchers used quantitative methods with primary data collection techniques, namely questionnaires distributed to 130 respondents. The data analysis technique used is multiple linear regression analysis using Jeffrey's Amazing Statistics Program (JASP). From the results of the research and discussion it is known that internal factors influence the decision to invest in the Islamic capital market as shown by Tcount > Ttable with a value of 3,359 > 1,978 and a significance value of 0,001 < 0,05. External factors influence the decision to invest in the Islamic capital market, shown by Tcount > Ttable with a value of 5,727 > 1,978 and a significance value < 0.001 less than 0,05. Simultaneously, internal factors and external factors influence the decision to invest in the sharia capital market for students of the Sharia Economics Study Program at UIN Fatmawati Sukarno Bengkulu by 43,7% and the significant probability value is < 0,001 less than 0,05 and the Fcount > Ftable with a value of 51,103 > 3,07.